Approche spatiale d’un centre hospitalier, le CHU pédiatrique de Ouagadougou (Burkina Faso) - Aude Nikiema (EchoGéo, 2014)
In geography, hospital is rarely observed at small scale. Surveys in children’s hospital of Charles de Gaulle were the occasion to approach the places which compose the hospital. The organization of the establishment is described and axes of movement were observed. The objective is to include elements which compose the therapeutic landscape and to define a model of organization.